Involvement of Fusobacterium nucleatum in malignancies except for colorectal cancer: A literature review - He, Zhixing; Tian, Wei; Wei, Qichun; Xu, Jing (Frontiers in Immunology, 2022)
Fusobacterium nucleatum (F. nucleatum) is originally an oral opportunistic pathogen and accumulating evidence links the presence of F. nucleatum with the pathogenicity, development, and prognosis of colorectal cancer (CRC). However, only limited preliminary data is available dealing with the role of F. nucleatum in other malignancies except for CRC. The present review aims to update and systematize the latest information about the mechanisms of F. nucleatum-mediating carcinogenesis, together with the detection rates, clinicopathological, and molecular features in F. nucleatum-associated malignancies. Comparing with adjacent non-tumorous tissue, previous studies have shown an overabundance of intratumoural F. nucleatum. Although the prognostic role of F. nucleatum is still controversial, a higher prevalence of F. nucleatum was usually associated with a more advanced tumor stage and a worse overall survival. Preliminary evidence have shown that epithelial-to-mesenchymal transition (EMT) and relevant inflammation and immune response aroused by F. nucleatum may be the probable link between F. nucleatum infection and the initiation of oral/head and neck cancer. Further studies are needed to elucidate the etiologic role of the specific microbiota and the connection between the extent of periodontitis and carcinogenesis in different tumor types. The mechanisms of how the antibiotics exerts the critical role in the carcinogenesis and antitumor effects in malignancies other than CRC need to be further explored.